Adapting the Trials of Improved Practices (TIPs) approach to explore the acceptability and feasibility of nutrition and parenting recommendations: what works for low‐income families?. Issue 4 (13th September 2013) - Dickin, Katherine L.; Seim, Gretchen
Abstract Interventions to prevent childhood obesity must consider not only how child feeding behaviours are related to child weight status but also which behaviours parents are willing and able to change. This study adapted Trials of Improved Practices (TIPs) to assess acceptability and feasibility of nutrition and parenting recommendations, using in‐depth interviews and household trials to explore families' experiences over time. A diverse sample of 23 low‐income parents of 3–11‐year‐olds was recruited following participation in nutrition and parenting education. Parents chose nutrition and parenting practices to try at home and were interviewed 2 weeks and 4–6 months later about behaviour change efforts. Qualitative analysis identified emergent themes, and acceptability and feasibility were rated based on parents' willingness and ability to try new practices. The nutrition goal parents chose most frequently was increasing children's vegetable intake, followed by replacing sweetened beverages with water or milk, and limiting energy‐dense foods. Parents were less inclined to reduce serving sizes. The parenting practices most often selected as applicable to nutrition goals were role‐modelling; shaping home environments, often with other adults; involving children in decisions; and providing positive feedback. Most recommendations were viewed as acceptable by meaningful numbers of parents, many of whom tried and sustained new behaviours. Food preferences, habits and time were common barriers; family resistance or food costs also constrained some parents. Despite challenges, TIPs was successfully adapted to evaluate complex nutrition and parenting practices. Information on parents' willingness and ability to try practices provides valuable guidance for childhood obesity prevention programmes.